2023
DOI: 10.1002/iid3.787
|View full text |Cite
|
Sign up to set email alerts
|

Limonin ameliorates indomethacin‐induced intestinal damage and ulcers through Nrf2/ARE pathway

Abstract: Background Nonsteroidal anti‐inflammatory drugs (NSAIDs) can cause intestinal damage and ulcers and the incidence is increasing. Limonin plays an important role in the regulation of inflammatory diseases, but it has not been reported in the treatment of intestinal injury and ulcers. Methods Indomethacin (INDO) induced intestinal injury and ulcer model in rats. The indexes related to intestinal injury were detected. Western blot and molecular docking techniques were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Limonin, a limonoid belonging to the triterpenoid group, is a bitter component of citrus seeds and fruit tissues. The unheated yuzu seed oil used in this study contained limonin, which has been shown to regulate the expression of various cytoprotective enzymes such as heme oxygenase-1 (HO-1) and NAD(P)H quinone oxidoreductase 1 (NQO1) by activating the Nrf2/ARE pathway [ 27 , 28 , 29 ]. Moreover, inducing the Nrf2/HO-1 signaling pathway inhibits inflammatory AD in skin keratinocytes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limonin, a limonoid belonging to the triterpenoid group, is a bitter component of citrus seeds and fruit tissues. The unheated yuzu seed oil used in this study contained limonin, which has been shown to regulate the expression of various cytoprotective enzymes such as heme oxygenase-1 (HO-1) and NAD(P)H quinone oxidoreductase 1 (NQO1) by activating the Nrf2/ARE pathway [ 27 , 28 , 29 ]. Moreover, inducing the Nrf2/HO-1 signaling pathway inhibits inflammatory AD in skin keratinocytes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…*p < 0.05, **p < 0.01, ***p < 0.001. (Gu et al, 2019;Jia et al, 2023). Some studies have found that adenine induced damage extends beyond the kidneys to affect the intestine as well, and the intestinal microbiota is a key mediator of the chemical's toxicological effects.…”
Section: The Influence Of Processing Factors On Ef Regulation Of Inte...mentioning
confidence: 99%
“…28 Limonin also ameliorated indomethacin-induced intestinal damage and ulcers. 29 Noteworthily, limonin significantly reduced serum TC and TG levels in obese mice 30 and diminished the accumulation of lipid droplets in the liver, in addition to downregulating the levels of lipogenic transcription factors FASN and SREBP1 in non-alcoholic fatty liver disease (NAFLD). 31 Yet, it remains unclear whether limonin's improvement of dyslipidemia is related to the regulation of the gut barrier and gut microbiota.…”
Section: Introductionmentioning
confidence: 99%